Neurobiological mechanisms involved in maternal deprivation-induced behaviours relevant to psychiatric disorders - Zanta, Natália Cristina; Assad, Nadyme; Suchecki, Deborah (Frontiers in Molecular Neuroscience, 2023)
Parental care is essential for proper development of stress response and emotion-related behaviours. Epidemiological studies show that parental loss in childhood represents a major risk factor for the development of mental disorders throughout the lifespan, including schizophrenia, depression, and anxiety. In most mammalian species, the mother is the main source of care and maternal behaviours regulate several physiological systems. Maternal deprivation (DEP) for 24 h is a paradigm widely used to disinhibit the hypothalamic–pituitary–adrenal axis response to stress during the stress hyporesponsive period. In this mini-review we will highlight the main DEP-induced neurobiological and behavioural outcomes, including alterations on stress-related hormones, neurogenesis, neurotransmitter/neuromodulatory systems and neuroinflammation. These neurobiological changes may be reflected by aberrant behaviours, which are relevant to the study of mental disorders. The evidence indicates that DEP consequences depend on the sex, the age when the DEP takes place and the age when the animals are evaluated, reflecting dynamic plasticity and individual variability. Individual variability and sex differences have a great relevance for the study of biological factors of stress resilience and vulnerability and the DEP paradigm is a suitable model for evaluation of phenotypes of stress- and emotion-related psychopathologies.